How DFID learns - ICAI (Independent Commission for Aid Impact (ICAI), 2014)
Excellent learning is essential for UK aid to achieve maximum impact a nd value for money. We take learning to mean the extent to which DFID uses information and experience to influence its decisions. Each ICAI review assesses how well learning takes place. Our reports to date ind icate a mixed performance. This review seeks to identify the way DFID learns and what inhibits it from doing so consistently. We drew on our reviews, assessed data from DFID’s own surveys and carried out interv iews inside and outside the department. Review DFID generates consider able volumes of information, much of which, such as funded research, i s publicly available. DFID does not clearly or consistently link this investment to how it can deliver better impact. We made five recommend ations and gave an amber-red score. Findings DFID does not clearly ide ntify how its investment in learning links to its performance and deli vering better impact. DFID has the potential to be excellent at organi sational learning if its best practices become common. DFID staff lear n well as individuals. They are highly motivated and DFID provides opp ortunities and resources for them to learn. DFID is not yet, however, managing all the elements that contribute to how it learns as a single , integrated system. DFID does not review the costs, benefits and impa ct of learning. Insufficient priority is placed on learning during imp lementation. The emphasis on results can lead to a bias to the positiv e. Learning from both success and failure should be systematically enc ouraged. Recommendations DFID needs to focus on consistent and continu ous organisational learning based on the experience of DFID, its partn ers and contractors and the measurement of its impact, in particular d uring the implementation phase of its activities. All DFID managers sh ould be held accountable for conducting continuous reviews from which lessons are drawn about what works and where impact is actually being achieved for intended beneficiaries. All information commissioned and collected (such as annual reviews and evaluations) should be synthesis ed so that the relevant lessons are accessible and readily usable acro ss the organisation. The focus must be on practical and easy-to-use in formation. Knowhow should be valued as much as knowledge. Staff need t o be given more time to acquire experience in the field and share less ons about what works and does not work on the ground. DFID needs to co ntinue to encourage a culture of free and full communication about wha t does and does not work. Staff should be encouraged always to base th eir decisions on evidence, without any bias to the positive.